Augmented Community Telerehabilitation Intervention to Improve Outcomes for People With Stroke. ACTIV: A Randomised Controlled Trial and Qualitative Enquiry - Saywell, Nicola Lesley (Auckland University of Technology, 2016)
For people to achieve and maintain the best possible outcomes after stroke, a level of rehabilitation input is required that cannot be met by current services. Telerehabilitation, the provision of rehabilitation at a distance using telecommunication technology, has been proposed as a way to extend the reach of rehabilitation, particularly to those for whom geography, poverty or disability preclude easy access to rehabilitation facilities. The difficulty with many potential modes of delivering telerehabilitation, is that they are expensive and complex, requiring significant technical input for satisfactory use. The use of readily-accessible telecommunication technology (landline telephones or mobile phones) to deliver stroke rehabilitation remotely was mooted as a possible solution, based on findings of feasibility and acceptability of use, in a number of small-scale studies in other populations. The idea was investigated using a systematic review, which showed that while mobile phones were almost ubiquitous in New Zealand, there had been minimal investigation of their use in stroke rehabilitation. A novel intervention was developed, based on the literature review and the clinical experience of the research team. Augmented Community Telerehabilitation Intervention (ACTIV) is a structured 6-month programme, delivered by physiotherapists using a combination of face-to-face sessions, telephone contact and text message reminders to support rehabilitation for people following stroke after standard rehabilitation has ended. A randomised controlled trial was undertaken, to compare the effectiveness of ACTIV with a usual care control, to improve outcomes for people with stroke. Measures of physical function and self-efficacy were taken immediately after ACTIV and 6-months after the end of the programme. A qualitative enquiry was also undertaken with a sample of those who had completed ACTIV, to explore the participant experience. The results of the trial showed that ACTIV improved physical function in people undertaking ACTIV as long as they undertook at least 50% of the programme. However, the significant improvement in physical function immediately after the programme was not sustained 6-months after cessation. A significant improvement was found in participation immediately after ACTIV, which also was not sustained at 6-months post-intervention. The qualitative enquiry showed that despite the first impression of ACTIV not being proper physiotherapy, there was a strong message that participants felt they had not been left to struggle alone and gained a number of benefits from the therapeutic relationship they developed with the physiotherapist during ACTIV. Participants also communicated strong feelings of making progress and a very clear impression of knowing what they wanted from rehabilitation. This was not the participant-generated goals, decided with the physiotherapists at the start of the programme, but a desire to keep on making small forward steps towards normality. Findings from the ACTIV study showed that a small input can make a significant difference for people after stroke but that the longed for behaviour-change leading to absolute independence from any support may be an unrealistic expectation. ACTIV may need to be extended in partnership with non-governmental agencies to continue a level of support that ensures benefits are maintained.
Keywords: Telerehabilitation; Stroke; RCT; Qualitative